Pemanfaatan SIG dalam Pemetaan Tutupan Lahan sebagai Suplemen Pembelajaran Geografi SMA Kelas X - Mohamad Alfian Laudji; Sri Maryati; M. Iqbal Liayong Pratama (-, 2026)
Land cover change in artificial lake buffer zones is a common phenomenon driven by increasing human activities, such as settlement expansion, agricultural development, and infrastructure construction. These changes have the potential to reduce the ecological function of lake areas as environmental buffer zones and to intensify hydrological problems, including sedimentation and declining water quality. This study aims to utilize Geographic Information Systems (GIS) as an instructional medium for Grade X senior high school geography through a case study of land cover change mapping in the Danau Perintis area, Bone Bolango Regency. The research employed a GIS-based spatial analysis approach using remote sensing image interpretation and overlay techniques on land cover maps from two different time periods. The results indicate significant land cover changes, particularly the conversion of natural vegetation into built-up and agricultural land. The use of GIS-based maps as supplementary learning materials has been shown to improve students’ understanding of environmental dynamics, the relationship between human activities and spatial changes, and spatial thinking skills. Therefore, GIS can be utilized as a contextual and applicable learning medium in geography education.